THE EFFECT OF QUALITY PAI MGMP ACTIVITIES ON PROFESSIONAL COMPETENCE AND PERFORMANCE OF PAI TEACHERS - Oki Dermawan; Muhammad Hafiz Alpami; Adri Efferi; I’anatut Thoifah (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
Subject Teachers working group (MGMP) is an educational organization which purpose is to improve the competence and professionalism of teachers to improve the quality of education. The quality of the Islamic Education (PAI) (MGMP) activities is a dynamic condition interrelated with the administration, teachers, processes and activities that comply with or exceed what expected. The quality of MGMP activities will help build professional competence and indirectly the performance of teachers. This study aimed to prove: (1) The influence of the quality of the PAI MGMP activities on the professional competence of teachers at the State Junior High Schools (SMPN) in Bandar Lampung. (2) The influence of professional competence on teacher performance at the SMPN in Bandar Lampung. (3) The indirect effect of the quality of the PAI MGMP activities on teacher performance at the SMPN in Bandar Lampung. (4) The influence of the quality of the PAI MGMP activities on professional competence with a teacher performance at the SMPN in Bandar Lampung. The approach in this research was quantitative research with the type was survey research. The data analyzed were parametric analysis with multiple linear regression analysis models (Multiple Linear Regression) using SPSS for Windows20.0. Data were collected from each variable separately by filling out a compiled questionnaire. The sample in this study were 57 teachers who were randomly assigned (cluster-random sampling). The results showed that, firstly, there was a significant influence on the quality of MGMP activities on the professional competence of teachers at the State Junior High School level in Bandar Lampung. Secondly, there was a significant effect of professional competence on teacher performance of teachers at the SMPN in Bandar Lampung. Thirdly, there was an indirect effect the quality of the PAI MGMP activities on the performance of teachers of SMPN in Bandar Lampung, and fourth, there is a significant influence on the quality of the PAI MGMP activities on professional competence and the performance of teachers at the SMPN in Bandar Lampung.